Lower Urinary Tract Symptoms in a Chronic Pelvic Pain Population. Issue 11 (November 2020) - Sammarco, Anne G.; Kobernik, Emily K.; Haefner, Hope K.; Till, Sara R.; Berger, Mitchell B.
Abstract : Objectives: This study aimed to characterize the prevalence of lower urinary tract symptoms in a chronic pain population. Methods: In this observational cohort study, patients referred to a female pelvic pain clinic completed several validated questionnaires assessing bladder symptoms, central sensitization, pain symptoms, depression, anxiety, and neuropathic pain. Patients diagnosed as having interstitial cystitis were excluded. Patient demographic characteristics and survey responses were compared across American Urological Association Symptom Index (AUA-SI) severity categories. Multivariable logistic regression was performed to identify independent predictors of moderate-to-severe AUA-SI scores. Results: A total of 177 patients were included in the analysis. American Urological Association Symptom Index data showed that 48.8% of patients had mild, 31.2% had moderate, and 20.0% had severe symptoms. Patients reporting moderate or severe AUA-SI scores had higher mean Central Sensitization Inventory (CSI) scores (46.7 ± 16.0 vs 32.9 ± 13.8, P < 0.0001), McGill scores (median, 25 [interquartile range, 16–38] vs 13 [5–27]; P = 0.0003), Patient-Reported Outcomes Measurement Information System depression T-scores (median, 53.9 [interquartile range, 46.2–61.6] vs 51.2 [37.1–55.3]; P = 0.009), Pelvic Pain and Urgency/Frequency Symptoms Scale scores (18.4 ± 6.2 vs 12.5 ± 5.4, P < 0.0001), and Self-Administered Leeds Assessment of Neuropathic Symptoms and Signs scores (median, 10.5 [interquartile range, 3.0–16.5] vs 6.0 [1.0–12.0]; P = 0.02). The odds of moderate-to-severe AUA-SI symptoms were higher with a positive PUF and CSI score and were lower with a diagnosis of vestibular pain. Conclusions: There is a high prevalence of lower urinary tract symptoms among patients with chronic pelvic pain. Vestibulodynia was associated with lower odds of bladder symptoms. High PUF and CSI scores were significantly associated with moderate-to-severe bladder symptoms.